2012
DOI: 10.1371/journal.pone.0051653
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Shedding Characteristics of Seasonal Influenza Virus (Sub)Types and Influenza A(H1N1)pdm09; Germany, 2007–2011

Abstract: BackgroundInfluenza viral shedding studies provide fundamental information for preventive strategies and modelling exercises. We conducted a prospective household study to investigate viral shedding in seasonal and pandemic influenza between 2007 and 2011 in Berlin and Munich, Germany.MethodsStudy physicians recruited index patients and their household members. Serial nasal specimens were obtained from all household members over at least eight days and tested quantitatively by qRT-PCR for the influenza virus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
104
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 36 publications
9
104
0
5
Order By: Relevance
“…shedding in influenza B patients treated with laninamivir (Ikematsu et al 2014a, b). Nonetheless, a German study reported that the period of viral RNA shedding, as determined by real-time PCR, was around 6-8 days and that there were no significant differences in duration between virus types or subtypes (Suess et al 2012). In addition, the authors found that the duration of detectable virus shedding was longer for real-time PCR than for virus culture-for both influenza A(H3N2) and B-as was the case in the present study.…”
Section: Discussionsupporting
confidence: 52%
“…shedding in influenza B patients treated with laninamivir (Ikematsu et al 2014a, b). Nonetheless, a German study reported that the period of viral RNA shedding, as determined by real-time PCR, was around 6-8 days and that there were no significant differences in duration between virus types or subtypes (Suess et al 2012). In addition, the authors found that the duration of detectable virus shedding was longer for real-time PCR than for virus culture-for both influenza A(H3N2) and B-as was the case in the present study.…”
Section: Discussionsupporting
confidence: 52%
“…What this study adds is the additional information of the comprehensive burden of all‐influenza cases in primary care, be they mild or more severe, not only by age, but also by type/subtype, over a long time period. It is interesting that the “typical” pattern of influenza B shows a substantially higher relative iMAARI attack rate among school‐age children5, 6, 7, 8, 9, 10, 11, 12, 13, 14 compared to that in age group 0‐4 (Figure 5, right panel), although in absolute terms the attack rate among 5‐ to 14‐year‐old children is comparable to that caused by A(H3N2). This striking characteristic of influenza B concurs with data from two serological studies, one from the Netherlands and one from Germany, which investigated the seroprevalence of antibodies against influenza virus types and subtypes by year of age among children 17, 18.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, in the three seasons following the pandemic, influenza‐associated consultations by patients with ILI were estimated in a population‐based surveillance project in 13 US health jurisdictions as 0.7%, 0.2% and 1.1% 16. Given that only between 30% and 80% of all influenza cases manifest themselves as ILI5, 6, 7, 8 and in the same year influenza seasons may be quite different in different countries, the estimated 2.6%, 1.0% and 8.9% in our study lie in a comparable magnitude as the US data. We believe that our combination of surveillance (using ARI data) followed by modelling estimates the population impact of influenza more realistically than sentinel systems that use ILI data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, if a good biomarker of infectivity is available, it might be advantageous simply to study the biomarker in a sample of influenza case patients, without having to follow up contacts of those patients. Viral shedding seems a natural candidate and has indeed been used as a proxy measure of infectivity in many studies [3][4][5][6][7][8][9][10][11]. One common approach is to use the duration of viral shedding as the infectious period.…”
mentioning
confidence: 99%